(untitled) (RuMoRes, 2009)
In this article are presented some considerations and introductory notes relating to an ongoing study in which we propose to examine and discuss the production of meaning in televisual language and more specifically in the genre of Brazilian miniseries. The alignment with the goals of the research will be made from the analysis of discoursive genres and themes of the miniseries Queridos Amigos. We seek to understand through discourse and themes of the miniseries the interrelationships of the circuit culturecommunication and its implications in developing an image of Brazil.